Pre-treatment of the beta3-adrenergic receptor agonist BRL37344 reduces in vivo myocardial ischemia/reperfusion injury by improving AMPK and SIRT1 activity and by suppressing mTOR and p70S6K signaling pathways - Ozek, Dilan Askin; Onat, Elif; Şahin, Kazım; Tuzcu, Mehmet; Bozoglan, Merve Yilmaz; Sahna, Engin (Univ Sao Paulo, Conjunto Quimicas, 2023)
This study aimed to investigate the role and signaling pathways of beta 3-AR in myocardial ischemia/reperfusion (I/R) injury, which is one of the leading causes of death worldwide. 47 male rats were randomly divided into two main groups to evaluate infarct size and molecular parameters. Rats in both groups were randomly divided into 4 groups. Control (sham), I/R (30 min ischemia/120 min reperfusion), BRL37344 (BRL) (A) (5 mu g/kg single-dose pre-treatment (preT) before I/R) and BRL (B) (5 mu g/kg/day preT for 10 days before I/R). Infarct size was determined with triphenyltetrazolium chloride staining and analyzed with ImageJ program. The levels of AMPK, SIRT1, mTOR, and p70SK6 responsible for cellular energy and autophagy were evaluated by western blot. Infarct size increased in the I/R group (44.84 +/- 1.47%) and reduced in the single-dose and 10-day BRL-treated groups (32.22 +/- 1.57%, 29.65 +/- 0.55%; respectively). AMPK and SIRT1 levels were decreased by I/R but improved in the treatment groups. While mTOR and p70S6K levels increased in the I/R group, they decreased with BRL preT. BRL preT protects the heart against I/R injury. These beneficial effects are mediated in part by activation of AMPK and SIRT1, inhibition of mTOR and p70S6K, and consequently protected autophagy.
Keywords: Adenosine monophosphate-activated protein kinase (AMPK); Beta3-adrenergic receptors; Myocardial Ischemia/Reperfusion; Mammalian target of rapamycin (mTOR); Sirtuin 1 (SIRT1)